Saxitoxin biosythesis genes (SXT) in the paralytic shellfish toxins-producing dinoflagellates, alexandrium species (Dinophyceae) - Law, Ing Kuo (Universiti Malaysia Sarawak (UNIMAS), 2013)
Saxitoxin (STX) is a neurotoxin that causes Paralytic Shellfish Poisoning (PSP). The toxin is produced by a group of marine eukaryotic dinoflagellates and prokaryotic cyanaobacteria. The toxin is accumulated in the edible shellfish and responsible for human intoxication after consumption. The biosynthetic gene,sxt/ is one of the genes involved in the PSP toxins biosynthetic pathway. The gene encodes O-carbomoyltransferase (OCASE) which was proposed to carbamoylate the hydroxyl-methyl side chain of the saxitoxin precursor. The present study was conducted to characterize the sxt genes in the marine dinoflagellates, Alexandrium species from Malaysian waters. Clonal cultures of Alexandrium species obtained from Harmful Algae Culture Collection, UNIMAS were used in this study. Toxicity of toxic and non-toxic Alexandrium species was confirmed by ELISA kit and HPLC method. Alexandriumminutum and A. tamiyavanichii were confirmed toxic, while A. leei, A. tamarense and A. tamutum are not toxic. A primer pair was insilico designed to screen for the presence of sxtI in both toxic and non-toxic Alexandrium species, the primer pair successfully amplified the gene from two toxic species, A. minutum and A. tamiyavancihii, with the amplicon size of around 200 bp, but was not detected in non-toxic .....Alexandrium species. This study revealed the presence of sxtI in toxic dinoflagellates.